2011
DOI: 10.1080/10590501.2011.577681
|View full text |Cite
|
Sign up to set email alerts
|

Should Atrazine and Related Chlorotriazines Be Considered Carcinogenic for Human Health Risk Assessment?

Abstract: Chloro-s-triazines have been a mainstay of preemergent pesticides for a number of decades and have generally been regarded as having low human toxicity. Atrazine, the major pesticide in this class, has been extensively studied. In a number of experimental studies, exposure to high doses of atrazine resulted in increased weight loss not attributable to decreased food intake. Chronic studies of atrazine and simazine and their common metabolites show an elevated incidence of mammary tumors only in female Sprague … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 113 publications
1
29
0
1
Order By: Relevance
“…Some toxic as Atrazine appears to interact strongly with a novel functional oestrogen transmembrane receptor, the G protein-coupled receptor 30 which is overexpressed in postpubertal germ cell tumours. 44,45 Other pathogenic processes could lead to spermatogenic defects. Environmental factors may either damage critical genes or alter gene expression by interfering with the epigenetic programming.…”
Section: Contribution Of Environmental Factorsmentioning
confidence: 99%
“…Some toxic as Atrazine appears to interact strongly with a novel functional oestrogen transmembrane receptor, the G protein-coupled receptor 30 which is overexpressed in postpubertal germ cell tumours. 44,45 Other pathogenic processes could lead to spermatogenic defects. Environmental factors may either damage critical genes or alter gene expression by interfering with the epigenetic programming.…”
Section: Contribution Of Environmental Factorsmentioning
confidence: 99%
“…However, later on, IARC removed atrazine from its list of suspected carcinogens (Jowa and Howd, 2011). Regardless of the various reports of atrazine effects on animals, the effects on humans are that due to a large oral dose of atrazine resulted in DNA lesions in the stomach, kidney, and liver of the rat (Pino et al, 1988).…”
Section: Carcinogenicitymentioning
confidence: 99%
“…However, a great number of epidemiological studies carried out with workers occupationally exposed to triazine herbicides indicate that these compounds do not have carcinogenic potential for these individuals. By analyses of different studies, it was observed that, although the chloro-s-triazine herbicides interfere in the endocrine responses of different species of mammals, their potential impact on humans seem to be mainly related to reproduction and development and not with human carcinogenesis [155].…”
Section: Harmful Effects Of Herbicides On Human Healthmentioning
confidence: 99%